Design And Implementation Of A Smart Office Network Module Using Visual Simulation Tool (Journal of Namibian Studies : History Politics Culture, 2023)
The modern era demands greater speed, efficiency, and quality in every aspect of life. Smart technologies, particularly the Internet of Things (IoT), have revolutionized the way people live and work. In this research paper, we explore the implementation of smart office technology, which includes connectivity and collaboration solutions, to enhance the productivity and safety of employees. For instance, smart parking systems enable employees to plan their commutes ahead of time, while smart meeting room solutions facilitate the selection of the most suitable meeting room for a team based on specific criteria. Furthermore, we discuss the use of IoT devices to limit natural pollution and adopt renewable energy in the office, such as air, sun, and rainwater harvesting. We also consider the implementation of a firewall in our server to ensure the security of our smart office network. By combining these smart concepts and systems, we can create a more efficient, secure, and eco-friendly workplace.